Partai Islam Se-Malaysia (PAS) dan Partai Keadilan Sejahtera (PKS) sebagai Partai Islam Pendukung Demokrasi PKS Pada Pemilu - Ahmad Ali Nurdin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The article compares the achievement of Partai Islam se-Malaysia (PAS) and Partai Keadilan Sejahtera (PKS) in the latest general election held in 2013 in Malaysia and in 2014 in Indonesia. The writer finds that the political performance of PAS and PKS has indicated differently contrast results. While political electability of PAS in the 2013 Malaysia’s general election has disappointed this party, PKS has successfully proved that surveys held by a number of survey institutes—predicting that the party would cease within the 2014 Indonesia’s national election—were totally false. Many political figures of PAS have failed to gain positions in the legislative assembly. Meanwhile, in viewing PKS’s political performance during the 2014 national election, one may assume that this party was luckily survive. This is because, a number of surveys conducted before the election had predicted that PKS could be considered lucky when it was able to gain five per cent of the vote, as its former president has been suspected of being corrupt for his involvement in cows import. However, the fact shows that PKS has magnificently survived, but it was even able to gain almost seven per cent of voters’ vote. Unfortunately, PKS was unsuccessful to achieve its political target to be the biggest three of the national vote.